ภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายโสธร เขต 1 - ศรีเนตร, นครินทร์; ลดาวัลย์, กฤตยากร (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด, 2023)
การวิจัยครั้งนี้มีวัตถุประสงค์ 1) เพื่อศึกษาภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายโสธร เขต 1 2) เพื่อเปรียบเทียบภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายโสธร เขต 1 จำแนกตาม ตำแหน่ง  วุฒิการศึกษา และ ประสบการณ์การทำงาน 3) เพื่อศึกษาข้อเสนอแนะเกี่ยวกับภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษายโสธร เขต 1 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารสถานศึกษาและครูผู้สอน จำนวน 302 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถามในการวิจัยได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน สถิติทดสอบค่าที (t-test) สถิติการวิเคราะห์ความแปรปรวนทางเดียว F-test (One-Way ANOVA) และการวิเคราะห์สถิติเชิงพรรณนา ผลการวิจัยพบว่า 1) ภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา โดยรวมอยู่ในระดับมาก 2) ความคิดเห็นที่มีต่อภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา จำแนกตามตำแหน่ง โดยรวมและด้านความยืดหยุ่น ด้านการไว้วางใจ แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ส่วนด้านจินตนาการ ด้านวิสัยทัศน์ ด้านการทำงานเป็นทีม ไม่แตกต่างกัน จำแนกตามวุฒิการศึกษาและประสบการณ์การทำงาน โดยรวมไม่แตกต่างกัน 3) ข้อเสนอแนะภาวะผู้นำเชิงสร้างสรรค์ของผู้บริหารสถานศึกษา ด้านจินตนาการ ผู้บริหารควรสร้างความเชื่อมั่น ความศรัทธา และความคาดหวังซึ่งก่อให้เกิดมโนภาพในจิตใจในการบริหาร ควรมีการแสดงออกถึงกระบวนการสร้างมโนภาพที่ชัดเจน ควรมีมุมมองหรือภาพอนาคตอย่างชัดเจนในการบริหาร ด้านความยืดหยุ่น ผู้บริหารควรมีการกระจายอำนาจการบริหารงานให้กับผู้ร่วมงาน ควรมีความพร้อมที่จะสร้างและรับสิ่งใหม่ๆ ที่จะเกิดขึ้นเพื่อนำมาพัฒนาสถานศึกษาให้มีประสิทธิภาพ และผู้บริหารควรปรับตัวได้ตามสถานการณ์ที่เปลี่ยนแปลง ด้านวิสัยทัศน์ ผู้บริหารควรมองภาพรวมที่เป็นไปได้ในอนาคตที่ทำให้เกิดการเปลี่ยนแปลงที่มุ่งสู่ความเป็นเลิศของสถานศึกษา ควรมีกระบวนการคิดที่เป็นไปได้ในอนาคตที่นำไปสู่การเปลี่ยนแปลงที่มุ่งสู่ความเป็นเลิศของสถานศึกษาควรมีการสนับสนุนให้บุคลากรพัฒนาตนเองอยู่เสมอ ด้านการทำงานเป็นทีม ผู้บริหารควรให้ความสำคัญกับความสามัคคีในสถานศึกษา ผู้บริหารควรมีการบริหารงานโดยยอมรับความร่วมมือจากทุกส่วนงาน ควรมีความเชื่อมั่นต่อเจตนาและความสามารถของบุคลากรในสถานศึกษา ส่วนด้านการไว้วางใจ ผู้บริหารควรรู้สึกเต็มใจหรือยินยอมที่จะกระทำตามข้อเสนอแนะของบุคลากรในสถานศึกษา ควรมีการบริหารงานโดยการเปิดโอกาสให้บุคลากรในสถานศึกษาได้แสดงความคิดเห็น และผู้บริหารควรมีการบริหารงานโดยยึดหลักความซื่อสัตย์สุจริต The objectives of this research were 1) to study the creative leadership of school administrators under Yasothon Primary Educational Service Area Office 1, 2) to compare the creative leadership of school administrators under the Yasothon Primary Educational Service Area Office 1, classified by position, educational background and work experience, and 3) to study recommendations on creative leadership of school administrators under Yasothon Primary Educational Service area Office 1. The sample group consists of 302 school administrators and teachers. The research tool applied is a questionnaire The statistics used were frequency, percentage, mean, and standard deviation. The t-test, and F-test (One-Way ANOVA) for analyzing variance and descriptive statistical analysis.            The results show that 1) The creative leadership of school administrators under the Yasothon Primary Educational Service Area Office 1 overall, it was at a high level, the aspect with the highest average to the lowest was imagination, followed by trust, teamwork, and flexibility. The side with the lowest average was vision. 2)  The comparison of opinion levels towards creative leadership of school administrators under the Yasothon Primary Educational Service Area Office 1, classified by position, overall and flexibility, and trust. The difference was statistically significant at the .05 level. In part of imagination, vision, teamwork no difference, classified by educational background and experience overall was not different. 3. Creative leadership recommendations of school administrators under the Yasothon Primary Educational Service Area Office 1 were 1) Imagination: administrators should build confidence, faith, and expectation which creates an image in the mind of management, there should be a clear representation of the visualization process, there should be a clear view or picture of the future in management. 2) flexibility, administrators should be decentralized to co-workers, readiness to create and receive new things that will happen for as to develop educational institutes to be effective, should be able to adapt according to changing situations.  3)  Vision: administrators should overview at possible in the future making changes aiming towards the the school excellence, should be a possible thinking process that lead to changes aiming towards the the school excellence, encouraging personnel to constantly develop themselves  4) Teamwork: administrators should pay attention to unity in educational institutions, should be an administration that accepts cooperation from all departments, should be confidence in attentions and abilities of personnel in education institutions  5) Trust: administrators should feel willing or agreeing with the recommendations of school personnel, should be administration by providing opportunities for personnel in educational institution to express their opinions, and should have management according to principles of honesty.